2006
DOI: 10.1007/s10495-006-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of HPV E6 proteins in preventing UVB-induced release of pro-apoptotic factors from the mitochondria

Abstract: Apoptotic elimination of UV-damaged cells from the epidermis is an important step in preventing both the emergence and expansion of cells with carcinogenic potential. A pivotal event in apoptosis is the release of apoptogenic factors from the mitochondria, although the mechanisms by which the different proteins are released are not fully understood. Here we demonstrate that UV radiation induced the mitochondrial to nuclear translocation of apoptosis inducing factor (AIF) in normal skin. The human papillomaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 46 publications
3
72
0
2
Order By: Relevance
“…Cell lines stably expressing HPV5 E6-HA mutants (derived from HT1080) were UVB irradiated at 1 m J cm 22 and harvested after 24 hr as described. Apoptosis assay cells were removed using trypsin and handled on ice.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lines stably expressing HPV5 E6-HA mutants (derived from HT1080) were UVB irradiated at 1 m J cm 22 and harvested after 24 hr as described. Apoptosis assay cells were removed using trypsin and handled on ice.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…21 We have previously shown that the HPV E6 protein of b-HPV types targets Bak for ubiquitin mediated degradation, 7 an E6 activity that prevents release of proapoptotic mitochondrial factors thereby maintaining mitochondrial integrity and function. 22 In marked difference to anogenital HPVs, b-type viruses such as HPV8 do not target p53 for proteolysis and do not interact with the E6-AP ubiquitin ligase utilized by anogenital HPV E6 proteins to signal p53 destruction. 23 Analysis of NMSC biopsies has also revealed that HPVnegative tumours have both a high apoptotic and proliferation rate compared to HPV-positive tumours that are also highly proliferative, but in contrast have a low apoptotic rate, in addition to significantly reduced levels of Bak.…”
mentioning
confidence: 99%
“…In addition, functional inactivation of p53 through activation of DNp73a has been detected in HPV38 E6E7-expressing human keratinocytes (Accardi et al, 2006). As the vast majority of SCCs are found on frequently UV-exposed skin and cumulative sun exposure is the most important known environmental SCC risk factor, the observation that HPV5 E6 eliminated UVBinduced apoptosis via degradation of Bak, thereby inhibiting the release of apoptosis-inducing factor, is particularly interesting Leverrier et al, 2007). This suggests that UV radiation-induced genotoxic DNA damage is potentially facilitated by bPVs (Bouwes Bavinck & Feltkamp, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Actinic keratosis is regarded as an early precancerous intraepidermal neoplasia, which represents the cutaneous counterpart of squamous intraepithelial lesions in the genital mucosa. Interestingly, the high prevalence and viral load of bPV types in these precancerous skin lesions Weissenborn et al, 2005) and the decrease in viral load during skin carcinogenesis may point to a particular involvement of HPV in the early stages of skin cancer development.Recent publications have demonstrated that bHPV-expressing keratinocytes can potentially facilitate UV radiationinduced DNA damage, as they are able to inhibit apoptosis in response to UV damage (Jackson & Storey, 2000;Leverrier et al, 2007;Struijk et al, 2008;Underbrink et al, 2008) and compromise the repair of UV-induced DNA mutations (Giampieri & Storey, 2004). These mechanisms may lead to the persistence of UV-damaged keratinocytes.…”
mentioning
confidence: 99%
“…Recent publications have demonstrated that bHPV-expressing keratinocytes can potentially facilitate UV radiationinduced DNA damage, as they are able to inhibit apoptosis in response to UV damage (Jackson & Storey, 2000;Leverrier et al, 2007;Struijk et al, 2008;Underbrink et al, 2008) and compromise the repair of UV-induced DNA mutations (Giampieri & Storey, 2004). These mechanisms may lead to the persistence of UV-damaged keratinocytes.…”
mentioning
confidence: 99%